Enhancing Cognitive Development in Learning Chemical Symbol and Periodicity through Instructional Game - Hassan Aliyu; Yasheni Raman; Corrienna Abdul Talib (International Journal of Asian Education, 2021)
A digital instructional game with embedded multimedia was believed not limited to allowing the learner to visualize chemistry concepts while playing but enable them to collect relevant information that connects the understanding of the other. The subject was described as a core science area with multiple macroscopic, submicroscopic, and symbolic representations. Thus, the study intended to investigate the effectiveness of the instructional game in enhancing students' cognitive development in learning chemical symbols and periodicity of elements. An instructional tool called "Symperiod Board Game) The study was designed and developed, containing 20 test items distributed in three different levels in order of complexity from simple to complex. The between-group experimental research design was adopted for this study in which 20 Form IV students distributed into four groups was selected. The alpha value 0.830 of the Pearson correlation coefficient determines the strength of the instrument's reliability, hence used for data collection. The data obtained were analyzed using descriptive statistics, and the results indicated that the cognitive development of the respondents' increases as students play the instructional game from level 1 to 3. Thus, the study reveals that a learner cannot understand a concept if he/she does not first remember it; similarly, he/she cannot apply knowledge and concepts if he/she does not understand them. It is imperative to conclude that the poor performance of students in chemistry can be associated with the quality of instruction provided by the teacher during classroom instructions.